Highest economic status increases risk of cesarean section in women of childbearing age - Idris, Haerawati; Anggraini, Rini (Faculty of Medicine, Universitas Trisakti, 2022)
BACKGROUNDCesarean section (CS) rates that are higher than the WHO recommendation may pose morbidity and mortality risks for both mother and child. In recent years, the number of CS deliveries has been increasing in developed and developing countries. The aim of the present study was to determine the rate of CS delivery and socioeconomic and demographic factors as risk factors of cesarean delivery in women of childbearing age. METHODSThis cross-sectional study used data from the 2017 Indonesian Health Demographic Survey (IDHS). The research subjects were 14,724 women of childbearing age aged 15-49 years who had given birth and met the inclusion criteria. The rate of CS was determined and the associations between independent and dependent variables were explored using logistic regression. RESULTSThe CS rate was 17.9%. Variables that had a significant relationship with cesarean delivery were geographic region, economic status, occupation, education, birth attendant, insurance ownership and antenatal care visits. The most dominant influencing variable was the highest economic status (OR 3.566; 95% CI: 2.857-4.452). Respondents with the highest economic status had a 3.5 times greater risk of having a cesarean delivery than subjects with the lowest economic status after controlling for the other variables. CONCLUSIONThis study demonstrated that the highest economic status increased the risk of CS delivery in women of childbearing age. The current epidemiological findings and evidence suggest adopting and implementing some strict guidelines in the health system to avoid unnecessary delivery by CS.